STUDI EVALUASI DIMENSI DAN PENULANGAN KOLOM BANGUNAN GEDUNG TERMINAL TIPE A DI SALATIGA - Hastu Tatas Herarkhi; Sumirin Sumirin; Rachmat Mudiyono (Pondasi, 2025)
The development of transportation infrastructure demands structural designs that are efficient, economical, and compliant with safety standards. Columns, as primary structural elements in buildings, play a critical role in supporting vertical loads and maintaining overall structural stability. This research aims to analyze and optimize the dimensions and reinforcement of columns in the Terminal Type A Building in Salatiga to achieve material efficiency without compromising structural strength. This study is based on the existing condition of the revitalized terminal building, taking into account gravitational and seismic loads in accordance with SNI 2847:2019 and SNI 1726:2019 standards. Structural analysis was conducted using building structure software to obtain the structural response and evaluate the strength of the column elements. Optimization was carried out by varying the column dimensions and reinforcement configurations to obtain the most efficient outcome in terms of concrete volume and reinforcement weight. The results of the study indicate significant potential for material savings while maintaining compliance with strength performance standards. The optimization process offers an alternative column design that is more economical and efficient, providing valuable reference for practitioners and academics in the planning of similar building structures.